1975
DOI: 10.1111/j.1476-5381.1975.tb07377.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Immediate Hypersensitivity Reactions in Laboratory Animals by a Phenanthroline Salt (Ici 74,917)

Abstract: 1 The activity of a new anti-allergic compound, I.C.I. 74,917, has been studied in the rat, mouse and guinea-pig.2 Following intravenous administration, I.C.I. 74,917 inhibits in a dose-dependent manner passive cutaneous anaphylaxis induced in rats and mice by heat-labile homocytotropic antibody. In rats, its potency is approximately 300 times that of disodium cromoglycate. 3 To achieve maximal inhibition, it is necessary to administer I.C.I. 74,917 at the same time as antigenic challenge; dosing before or aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Martin showed that the failure of SCG to inhibit guinea-pig PCA is not only limited to reactions mediated by the non-reaginic IgG, antibody, but also occurs with the newly-recognized guinea-pig reaginlike antibody. The failure of SCG to inhibit PCA reactions mediated by IgGl-antibodies was also reported by Lopez & Bloch (1969), Evans & Thomson (1975), and Taylor & Roitt (1973). Assem & Richter (1971) found that SCG inhibited both IgG1 and reagin-mediated histamine release from guinea-pig lung.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Martin showed that the failure of SCG to inhibit guinea-pig PCA is not only limited to reactions mediated by the non-reaginic IgG, antibody, but also occurs with the newly-recognized guinea-pig reaginlike antibody. The failure of SCG to inhibit PCA reactions mediated by IgGl-antibodies was also reported by Lopez & Bloch (1969), Evans & Thomson (1975), and Taylor & Roitt (1973). Assem & Richter (1971) found that SCG inhibited both IgG1 and reagin-mediated histamine release from guinea-pig lung.…”
Section: Discussionmentioning
confidence: 84%
“…Assem & Richter (1971) found that SCG inhibited both IgG1 and reagin-mediated histamine release from guinea-pig lung. Experiments with chopped lung produced variable results (Cox, 1967;Evans & Thomson 1975). Taylor & Roitt (1973), Carney (1976), andCatty &Fraser (1972), in experiments with guinea-pigs actively or passively sensitized, showed that suppression of IgE-mediated responses, either with SCG or by previous heat treatment of the antibody, potentiates cutaneous and pulmonary responses to antigen.…”
Section: Discussionmentioning
confidence: 99%
“…M&B 22948 was indeed introduced as an inhibitor of reagin-mediated anaphylaxis (Broughton, Chaplen, Knowles, Lunt, Pain, Wooldridge, Ford, Marshall, Walker & Maxwell, 1974). Similarly ICI 74917 inhibits immediate hypersensitivity reactions (Evans & Thomson, 1975), and selectively inhibits cyclic GMP hydrolysis (Coulson et al, 1977;Ruckstuhl & Landry, 1981). It must also be noted that DSCG is a highly selective inhibitor of cyclic GMP hydrolysis (Bergstrand, Kristofferson, Lundquist & Schurmann 1977;and Table 1) and has been previously shown to inhibit histamine release from mast cells but not from basophils (Assem & Mongar, 1970).…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently other compounds have been shown to possess similar inhibitory effects on immediate hypersensitivity responses. Of these,4,7,917) as the disodium salt (Figure 1) has been shown to be 300 times more potent than DSCG in inhibiting dermal blueing reactions provoked by Compound 48/80 in rats (Evans & Thomson, 1975). This novel compound also inhibits allergic bronchospasm in the guinea-pig in a dose dependent manner.…”
Section: Introductionmentioning
confidence: 95%